Intercultural advising for Chinese international students: a reflective inquiry. (15th March 2019) - Lin, Xiaobing; Liu, Wei
ABSTRACT: In the past decade, there has been a rapid increase in the number of Chinese international students studying overseas. There has also been a corresponding increase in the media stories about their cross-cultural difficulties. Reported in this study is a reflective inquiry into my work as an international student advisor with a large number of Chinese students in a top Canadian university. Through five composite stories, I hope to present a few areas of challenges Chinese students experience and reflect on how advisors can better support them from the intercultural perspective. I also hope to engage other advisors through this study in exploring ways to contribute to the field of international education as frontline practitioners.